2017
DOI: 10.1145/3057863
|View full text |Cite
|
Sign up to set email alerts
|

Exploring DIY Practices of Complex Home Technologies

Abstract: We are surrounded by increasingly complex networks of smart objects, yet our understanding and attachment to them is rather limited. One way to support stronger end users' engagement with such complex technologies is by involving them in the design process and, with the advent of Arduino prototyping platform, even in their making. While DIY practice offers the potential for stronger user engagement with physical artifacts, we know little about end users' DIY practice of making complex electronic technologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 80 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…We have presented different material qualities, their affordances and how they foster different reflections which designers can consider when deciding which such modalities. Future work will focus on building a DIY toolkit with modularized components [70] of different actuators that can be plugged and played with biosensors. Such kit may be used for codesigning with therapists to better tailor it to the needs of people living with affective disorders such as depression [60,68].…”
Section: Discussionmentioning
confidence: 99%
“…We have presented different material qualities, their affordances and how they foster different reflections which designers can consider when deciding which such modalities. Future work will focus on building a DIY toolkit with modularized components [70] of different actuators that can be plugged and played with biosensors. Such kit may be used for codesigning with therapists to better tailor it to the needs of people living with affective disorders such as depression [60,68].…”
Section: Discussionmentioning
confidence: 99%
“…Although weavers have initiatives to enlarge their business, they have mobility constraints having to work from home. This opens the design opportunities for novel tools requiring limited digital literacy [12] for empowering weavers through online presence to showcase their craft for reaching new customers. Such tools could also support weavers' access to supply chain so that they can collaboratively purchase affordable materials in bulk promoting a co-operative model for community-based enterprise in this developing context.…”
Section: Accessible Tools For Weavers' Online Presence and Access To mentioning
confidence: 99%
“…The distinction between novices' and expert's mental model is an important one, with consistent findings indicating that the latter is more accurate, complex, and abstract [11] [12][23] enabling a deeper understanding of the inner working of a system rather than merely how it can be used. In addition, a wealth of findings has shown that people have limited mental models of technological systems, such as personal or home technologies, including appliances [8][62] [67] or energy monitors [77]. Such systems tend to be operated from superficial functional models rather than structural ones.…”
Section: Mental Models In Hcimentioning
confidence: 99%
“…While much of previous work focused on mental models of interactive systems [6], learning environment [30] [44] or complex home technologies [77], much less work explored the mental models of large-scale distributed systems or technological infrastructures such as blockchain. We argue for a new approach to explore the mental models of such infrastructures by materializing them through physical representations.…”
Section: Mental Models In Hcimentioning
confidence: 99%